Toward the use of single crystal diamond based detector for ion-beam therapy microdosimetry. (March 2018) - Verona, C.; Magrin, G.; Solevi, P.; Bandorf, M.; Marinelli, M.; Stock, M.; Verona Rinati, G.
Abstract: In this work, the fabrication and characterization of a microdosimeter based on a synthetic single crystal diamond is reported. The microdosimeter is realized by means of both standard photolithography and selective chemical vapor deposition techniques to accurately define its micrometric sensitive volume. Experimental measurements were carried out at the Ruđer Bošković Institute microbeam facility using different particles such as proton, helium, lithium, carbon and oxygen. Ion beam induced charge (IBIC) technique was performed to characterize the microdosimeter response in terms of its charge collection properties. The experimental data were also analyzed by means of Geant4 Monte Carlo simulations. Diamond based microdosimeter shows a well-defined active volume. Homogeneity of the response was estimated at about 7% and linked to structural defects of the diamond surface as deduced by AFM inspection. The detector response shows a good linear behavior for ions of different kind and energy, indicating that the detector is suitable for measuring a wide range of particles and LET i.e. 100 ÷ 3000 keV/μm. Finally, microdosimetric capabilities of the diamond based microdosimeter were preliminarily tested in low LET radiation fields (i.e. protons beam). Highlights: Fabrication of a novel design of diamond based microdosimeter. Characterization of the detector under micro-beams of proton, helium, lithium, carbon and oxygen. The detector shows a well-defined active volume with high spatial resolution. The detector response shows a linear behavior as a function of the LET of the incident particles. Microdosimetric spectra of 600 keV protons obtained with diamond detector are analyzed.